Potential Phytochemicals and Pharmacological Aspect of Ficus deltoidea Plant - Nafees, Sharbat Khan; Zaheen, Zahidullah; Khan, Mohammad Aziz (Journal for Research in Applied Sciences and Biotechnology, 2023)
Ficus deltoidea is a potential plant used for several purposes. This plant traditionally used for various treatment in the different parts of the globe. Ficus deltoidea has diversed morphology and mostly found in south Asian countries. Due to its great potential, recently it is getting famous as more attention given in exploring herbs as an alternative for medicine. The active phytochemicals of F. deltoidea have been studied for antioxidant, anti-diabetic, anti-inflammatory, antinociceptive, anti-ulcerogenic and wound healing activities. This review article will focus on to elaborate the active phytochemicals and pharmacological properties of F. deltoidea plant.